Privatization as a part of a Liberalization Program in an International Oligopoly - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2000)
This paper determines the equilibrium market structure in an international oligopoly which is opened up by a privatization. Market power is shown to be an important determinant of the equilibrium market structure, when greenfield investment costs are high. When the greenfield investment costs are low, however, the risk of monopolization decreases. It is also shown that 'Investment Guarantees' can be counterproductive by helping the buyer of the state assets prevent other investors from entering greenfield by credible over-investment. We also find that the negative effects on domestic firms by National Treatments clauses are partly paid for by the foreign investor in the bidding competition over the state assets.
Keywords: F23; L13; L33; 330; Privatization; FDI; Acquisitions; National Treatment; Investment Guarantees; Oligopol; International; Privatisierung; Marktstruktur; Marktmacht; Theorie